2020
DOI: 10.3390/ma13051084
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Hybrid Cement Based on Fly Ash, Metakaolin and Portland Cement Clinker

Abstract: Hybrid cement has become one of the most viable options in the reduction of CO 2 emissions to the environment that are generated by the cement industry. This could be explained by the reduction of the content of clinker in the final mixture and substitution of the remaining percentage with supplementary cementitious materials with the help of an alkaline activation. Following that, properties that are provided by an Ordinary Portland Cement and of a geopolymer are mixed in this type of hybrid material and coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…However, many fly ash-based geopolymers previously reported in the literature for different purposes and applications could be improved by applying the formulations developed in this study. These formulations could be used to improve the fly ash-based geopolymer coating for fire resistance materials [ 32 ], the immobilization of hazardous substances [ 25 ] and backfilling materials [ 71 ], low micro-filling effect (low porosity) materials [ 24 ], absorbent materials [ 44 ], or asphalt binders [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many fly ash-based geopolymers previously reported in the literature for different purposes and applications could be improved by applying the formulations developed in this study. These formulations could be used to improve the fly ash-based geopolymer coating for fire resistance materials [ 32 ], the immobilization of hazardous substances [ 25 ] and backfilling materials [ 71 ], low micro-filling effect (low porosity) materials [ 24 ], absorbent materials [ 44 ], or asphalt binders [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kaur et al [ 21 ] indicated that approximately 1.2 times more compressive strength could be obtained when a combination of NaOH and Na 2 SiO 3 was added to fly ash, compared to the use of NaOH only. The compressive strength increased as NaOH concentration increased from 8 to 16 M. Thus, the increase of NaOH concentration caused a significant acceleration of dissolution reactions, promoting the early stages of the geopolymerization process [ 24 , 25 ]. A maximum compressive strength of 40.42 MPa was obtained when fly ash was activated with 16 M NaOH and mixed with a sand to fly ash ratio of 3:1 [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A geopolymer hybrid is a combination of geopolymer and OPC or other binders, in order to produce material that combines the positive properties of OPC with the properties of alkali-activated materials or geopolymers. Hybrid OPC-geopolymer concrete has a lowered carbon footprint and improved ambient temperature curing while maintaining the positive properties of heavy metals immobilization, generally good mechanical properties, and high durability [50,51]. In the case of hybrid OPC-geopolymer concrete, generally of high FA content (70-90%) and low OPC content (10-30%), the clinker reaction products and reaction products from the glass phases of FA coexist.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, various waste products have been used to partially replace the original compounds that concretes are made of. These efforts are especially evident in the case of cement which is partially substituted by blast furnace slag [12,13], silica fume [14,15], fly ash [16,17] or other less energy-demanding material alternatives that exhibit certain pozzolanic properties. However, the primary resource savings can also be achieved in the case of other compounds such as aggregates.…”
Section: Introductionmentioning
confidence: 99%